Understanding Risk in an Evolving World : A Policy Note - Global Facility for Disaster Reduction and Recovery (World Bank, Washington, DC, 2014)
The foundation for DRM is understanding the hazards, and the exposure and vulnerability of people and assets to those hazards. By quantifying the risks and anticipating the potential impacts of hazards, governments, communities, and individuals can make informed prevention decisions. Such information can be used to set priorities for development and adaptation strategies, sector plans, programs, projects, and budgets.